Effect of two days treatment with orlistat on plasma leptin in obese patients without weight loss - Ana Rodríguez-Valle; María Ángeles Navarro-Ferrando; Diana Boj-Carceller; Jesús Fernando Escanero-Marcén; Alejandro Sanz-Paris (Nutrición Hospitalaria)
Objective: Little is known about the impact of orlistat on the leptin system. We studied the plasma leptin and satiety sensation response for two days of orlistat treatment without hypocaloric diet and weight loss. Material and methods: Twenty obese female subjects were recruited from our medical outpatient clinics. All of these subjects had previously received advice on dietary restriction and lifestyle modification, but remained obese with a stable body weight for at least six months before recruitment for the study. Results: Subjects were given 120 mg orlistat 3 times daily and were asked to maintain their usual diet. At baseline and two days after the treatment with orlistat, physical examination, hunger and blood analysis were repeated. There were no significant differences observed regarding energy dietary intake, body weight and waist-hip ratio, or in plasma glucose, insulin c-peptide concentrations. Only plasma leptin and triglycerides concentrations decreased (p: 0.0001 and 0.01 respectively). Decrease in plasma leptin concentration was positively correlated with changes observed in plasma triglycerides concentration (p: 0.01, r2: 0.45). Pre-dinner hunger increased and was negatively correlated with decrease in leptin (p: 0.0001, r2: 0.74) and triglycerides (p: 0.02, r2: 0.59). Conclusion: These data suggest that the partial fat malabsorption induced by the treatment with orlistat quickly reduces plasma triglycerides and leptin. This decrease is associated with increased appetite before intake following the main meal of the day.